People’s Participation in Preventing and Solving Prostitution in Amphoe Muang Chiang Mai, Chiang Mai Province - Tansakul, Permyot; Vivatthanaporn, Aranee (Suan Dusit Graduate School Academic Journal, 2022)
This research aimed to study the level of public participation in preventing and solving prostitution, the level of public opinion on the method of preventing and solving prostitution, and the influence of different personal factors on the level of public participation in preventing and solving prostitution and the level of public opinion on the method of preventing and solving prostitution in Amphoe Muang Chiang Mai, Chiang Mai province. The quantitative research methodology was employed in this research. The sample included 400 residents of Amphoe Muang, Chiang Mai. The content validity assessment was conducted and the Index of Item – Objective Congruence (IOC) ranged between 0.50-1.00. The reliability of the questionnaire was examined and the value of Cronbach’s alpha was at 0.872. The results found that the majority of samples were women rather than men, with the ages between 20-29 years old, being single, holding the highest degree as bachelor’s degree, working as government officials, government employees or in state enterprises, and earning between 10,000-19,999 baht per month. The overall level of public participation in preventing and solving prostitution was found at the low level. On the other hand, the level of public opinion on the method of preventing and solving prostitution was rated at the high level. The comparative study between different personal factors and public participation in preventing and solving prostitution and the level of public opinion on the method of preventing and solving prostitution showed that people with different occupation had different participation in preventing and solving prostitution at the statistical significance level of 0.05. In addition, people with different gender, age, marital status, and monthly salary had different level of public opinion on the method of preventing and solving prostitution at the statistical significance level of 0.05.